2020
DOI: 10.1093/mnras/staa3844
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the low-density H i intergalactic medium from z = 3.6 to 0: data, transmitted flux, and H i column density,,

Abstract: We present a new, uniform analysis of the H i transmitted flux (F) and H i column density ($N_{\mathrm{H\,{\small I}}}$) distribution in the low-density IGM as a function of redshift z for 0 < z < 3.6 using 55 HST/COS FUV (Δz = 7.2 at z < 0.5), five HST/STIS + COS NUV (Δz = 1.3 at z ∼ 1) and 24 VLT/UVES, and Keck/HIRES (Δz = 11.6 at 1.7 < z < 3.6) AGN spectra. We performed a consistent, uniform Voigt profile analysis to combine spectra taken with different instruments, to red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 95 publications
3
29
0
Order By: Relevance
“…The photoionisation rate required to match the observed CDDF 3 , Γ CDDF HI , is a factor of 0.4-0.6 times the P19 UV background model value at z = 0.1, suggesting that the P19 model may overproduce the UV background 3 We choose to match the CDDF over a limited range in N HI , rather than matching the mean or distribution of the Lyα forest transmission, as the CDDF is less susceptible to systematic uncertainties associated with signalto-noise and the uncertain properties of high density gas in the CGM. Nevertheless, we note the mean transmission associated with the rescaled CDDF -given in Table 1 -is in excellent agreement with F = 0.983 ± 0.009 at z = 0.08 from Kim et al (2021) at z ∼ 0.1. The simulations with a higher fraction of hot gas, either from additional physics (StrongAGN and Blazar) or from artificially increased photoheating rates (e.g.…”
Section: Comparison Of the Models To Cos Datasupporting
confidence: 72%
See 1 more Smart Citation
“…The photoionisation rate required to match the observed CDDF 3 , Γ CDDF HI , is a factor of 0.4-0.6 times the P19 UV background model value at z = 0.1, suggesting that the P19 model may overproduce the UV background 3 We choose to match the CDDF over a limited range in N HI , rather than matching the mean or distribution of the Lyα forest transmission, as the CDDF is less susceptible to systematic uncertainties associated with signalto-noise and the uncertain properties of high density gas in the CGM. Nevertheless, we note the mean transmission associated with the rescaled CDDF -given in Table 1 -is in excellent agreement with F = 0.983 ± 0.009 at z = 0.08 from Kim et al (2021) at z ∼ 0.1. The simulations with a higher fraction of hot gas, either from additional physics (StrongAGN and Blazar) or from artificially increased photoheating rates (e.g.…”
Section: Comparison Of the Models To Cos Datasupporting
confidence: 72%
“…In order to approximately forward model the COS data, all the simulated spectra are convolved with the COS line spread function 1 at 1341 Å, for central wavelength G130M/1327 at lifetime position LP1. The spectra are then rebinned onto pixels of width 0.02991 Å (i.e 3 times the COS binning of 0.00997 Å following Kim et al (2021)) and a Gaussian distributed signal-to-noise of S/N = 30 per 19 km s −1 resolution element (i.e. S/N ∼ 17.7 per pixel) is added.…”
Section: Simulated and Observed Lyα Forest Spectramentioning
confidence: 99%
“…Our study demonstrates again the key role that COS HST UV spectroscopy plays in our understanding of the low-z IGM. Given the time-sensitive state of HST's remaining mission, a focus on UV absorption now is critical to provide further constraints on the physical state of IGM gas covering the Lyα transition at 0.4 < z < 1.7, where the Lyα forest statistics transition from dark matter/UVB dominated to baryonic feedback/UVB dominated (see also Kim et al 2020). Bolton et al (2022) recently suggested that in order for the simulated and observed diffuse IGM Lyα b distribution to match, unresolved turbulent broadening at the ratio of b turb /b therm = 0.73 is needed.…”
Section: The Importance Of Agn Feedback On the Low-zmentioning
confidence: 99%
“…However, observing the Lyα forest at z 2 is substantially more challenging than at higher redshifts as it requires state-of-the-art spectrographs above Earth's atmosphere to reach the rest-frame far-ultraviolet (FUV) band (Danforth et al 2016;Gurvich et al 2017;Viel et al 2017;Christiansen et al 2020). Recent observations with the Cosmic Origins Spectrograph (COS) aboard the Hubble Space Telescope have enabled studies of the low-redshift Lyα forest in great statistical detail and with high sensitivity (Meiring et al 2011;Danforth et al 2016;Kim et al 2020). In particular, Danforth et al (2016, henceforth D16) built on the heritage of many previous low-z IGM absorber catalogs from HST/FOS (Bahcall et al 1996;Jannuzi et al 1998;Weymann et al 1998), HST/GHRS (Penton et al 2000), FUSE (Danforth & Shull 2005), and HST/STIS (Penton et al 2004;Lehner et al 2007;Tripp et al 2008;Danforth et al 2010;Tilton et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At redshifts 𝑧 H I < 0.2, corresponding to 𝑧 = 3.0-3.8 for He II, there are on average 5 H I absorbers with log 𝑁 H I = 14-17(Kim et al 2021) per line of sight. Each of these absorbers has an optical depth at the Ly𝛼 line center 𝜏 H I > 1.7 and full width at half maximum ∼ 0.3 Å after accounting for the COS line-spread-function.…”
mentioning
confidence: 99%